2008
DOI: 10.1375/twin.11.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Specific Intrauterine ‘Growth’ Charts Based on Cross-Sectional Birthweight Data

Abstract: The assessment of fetal growth is an essential component of good antenatal care, especially for twins. The aims of this study are to develop twin-specific intrauterine 'growth' charts, based on cross-sectional birthweight data, for monochorionic and dichorionic twins according to sex and parity, and to detect twins at risk for neonatal death by comparing the use of twin-specific and singleton charts. The study sample consisted of 76,471 singletons and 8454 twins (4227 pairs) born in East Flanders (Belgium). Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Data on placentation were obtained, when available, from the original pathological report of the placenta. Birthweight centiles were calculated according to Gielen et al 29 Zygosity was established with the use of PowerPlex 16 (Promega Corporation, Madison, WI, USA). Zygosity testing was performed on DNA isolated from buccal swabs when available; in all other cases, it was performed on DNA isolated from blood lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on placentation were obtained, when available, from the original pathological report of the placenta. Birthweight centiles were calculated according to Gielen et al 29 Zygosity was established with the use of PowerPlex 16 (Promega Corporation, Madison, WI, USA). Zygosity testing was performed on DNA isolated from buccal swabs when available; in all other cases, it was performed on DNA isolated from blood lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Although in almost all cases the genetic defect is demethylation of DMR2, relative birthweight centiles were calculated for or against twin referents. 29 Of the three major criteria, macrosomia (birthweight above birth weight centile P9), macroglossia and abdominal wall defects, macrosomia was present only in 5 of the 11 affected twins (twins 6, 7, 11 and 13). In 4 of 10 cases, the unaffected twin had a higher birthweight compared with the affected twin (twins 1, 3B, 9 and 10).…”
Section: Phenotypementioning
confidence: 99%
“…Other studies have demonstrated reduced weight gain after the 32nd week of pregnancy, but reduced height gain only after week 39 [van Dommelen et al, 2008] Belgian twin pregnancies were used to create prenatal ''growth curves,'' used to monitor growth throughout the pregnancy, and to predict those at risk of neonatal death. [Gielen et al, 2008].…”
Section: Growthmentioning
confidence: 99%
“…Twin pregnancies are high-risk gestations with elevated perinatal mortality rates [1] . Twins, when compared with singletons, have a five-fold risk of fetal death, seven-fold elevated risk of neonatal death, and five-fold risk of infant death [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Twins also respond differently from singletons to interventions that are designed to lengthen the gestational age at birth [5,6] . Factors that impact fetal mortality risks include prenatal complications, maternal age, poor obstetric history and Assisted Reproductive Technology (ART) [1][2][3][4][5][6]. Twins face greater risks for low birth weight, preterm birth, long-term disability and early death than singletons [7].…”
Section: Introductionmentioning
confidence: 99%